Advances in Chemistry and Bioactivity of the Genus Chisocheton Blume. Issue 5 (May 2016) - Shilpi, Jamil A.; Saha, Sanjib; Chong, Soon‐Lim; Nahar, Lutfun; Sarker, Satyajit D.; Awang, Khalijah
Abstract : Chisocheton is one of the genera of the family Meliaceae and consists of ca . 53 species; the distribution of most of those are confined to the Indo‐Malay region. Species of broader geographic distribution have undergone extensive phytochemical investigations. Previous phytochemical investigations of this genus resulted in the isolation of mainly limonoids, apotirucallane, tirucallane, and dammarane triterpenes. Reported bioactivities of the isolated compounds include cytotoxic, anti‐inflammatory, antifungal, antimalarial, antimycobacterial, antifeedant, and lipid droplet inhibitory activities. Aside from chemistry and biological activities, this review also deals briefly with botany, distribution, and uses of various species of this genus. Abstract :